Correction: Chen et al. The Protective Effect of Mangiferin on Formaldehyde-Induced HT22 Cell Damage and Cognitive Impairment. Pharmaceutics 2023, 15, 1568 - Fan Chen; Na Wang; Xinyan Tian; Juan Su; Yan Qin; Rongqiao He; Xiaping He (Pharmaceutics)
In the original publication [...]